DINAMIKA PELAKSANAAN KEBIJAKAN PEMERINTAH DALAM PENANGGULANGAN KEMISKINAN DI INDONESIA - Dian Novita Fajar Sari; Yofitri Heny Wahyuli; Andela Anggleni (Jurnal STIA Bengkulu, 2023)
Poverty Reduction Policies here have a very strategic role in efforts to increase poverty reduction in Indonesia. Various programs have been created and run by the government in various forms over a long period of time. However, in the implementation phase of the policy, it turns out that there are still many obstacles and obstacles. The distribution of social assistance that has not been properly targeted (distribution bias) is one of the main problems that must be immediately found the best solution. This distribution bias is caused by the discretion of the program implementing officers in the field (street-level bureaucracy). This condition has had an impact on the achievement of the poverty reduction target which has not been optimal.